2014
DOI: 10.1016/j.juro.2013.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Risk Alleles are Associated with Prostate Cancer Volume and Prostate Size

Abstract: Purpose Genome-wide association studies have identified an increasing number of single nucleotide polymorphisms (SNPs) associated with prostate cancer risk. Some of these same genetic variants are also associated with serum PSA levels and lower urinary tract symptoms, raising the question whether the SNPs are truly biomarkers for prostate cancer or simply lead to detection bias. We therefore sought to determine whether the prostate cancer risk SNPs are more strongly associated with tumor volume or prostate vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…These genomic aberrations result in altered mRNA expression levels in tumour versus normal tissues (Figure 3(b)). Additionally, three of these genes ( MYC, KLF10 and PTK2 ) are located in a region of genomic instability on chromosome 8, which is associated with poor prognosis [37–39]. A detailed analysis of the chromosomal loci 8q, 10q and 14q, which harbour these genes, confirmed the presence of gross CN aberrations in both PC3 cells and L‐EVs (Figure 3(c)).…”
Section: Resultsmentioning
confidence: 98%
“…These genomic aberrations result in altered mRNA expression levels in tumour versus normal tissues (Figure 3(b)). Additionally, three of these genes ( MYC, KLF10 and PTK2 ) are located in a region of genomic instability on chromosome 8, which is associated with poor prognosis [37–39]. A detailed analysis of the chromosomal loci 8q, 10q and 14q, which harbour these genes, confirmed the presence of gross CN aberrations in both PC3 cells and L‐EVs (Figure 3(c)).…”
Section: Resultsmentioning
confidence: 98%
“…Given that MRI can visualize anatomical structure better than ultrasound, MRI‐based measurements of prostate volume and the derived PSA density were more accurate in our study compared with ultrasound‐based measurements. Reinhardt et al reported that tumor volume exhibited an association with genetic risk of PCa . In our study, all this information was included in risk modeling.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have identified associations between SNPs within or near the PSA gene ( KLK3 ) and high-grade tumors and adverse clinical outcomes (Bensen et al 2013; Cramer et al 2008; Gudmundsson et al 2010; Lindstrom et al 2011; Reinhardt et al 2013; Slager et al 2003; Xu et al 2008). For example, using cohorts of European and Ashkenazi Jewish ancestry, two studies found that SNP rs2735839 in KLK3 was associated with PC-specific mortality (Gallagher et al 2010; Pomerantz et al 2011).…”
Section: Discussionmentioning
confidence: 99%